PENGARUH PENTING AGAMA DAN TRADISI SPIRITUAL DALAM MEMBENTUK IDENTITAS PSIKOLOGIS MASYARAKAT SASAK DI LOMBOK - Danang Nur Adiwibawa (Yayasan Nusantara Hasana Berdikari, 2024)
This study seeks to explore how religion and spiritual customs contribute to the formation of the psychological identity of the Sasak people in Lombok. The Sasak people are known for their deep connection to Islamic religious values ​​and a series of local traditions that have been passed down from generation to generation. This study used a survey method involving 20 Sasak community respondents. A specially designed questionnaire was used to investigate the impact of religion and local culture on the formation of self-identity, providing emotional support, and fostering social relationships. Data were carefully analyzed descriptively, qualitatively and quantitatively to increase understanding of the importance of religion and local culture as spiritual traditions in the lives of the Sasak people. The findings of this study reveal that religion plays a significant role in shaping one's psychological identity. It primarily offers peace, emotional balance, and purpose in life. In addition, local cultural customs and other traditional practices foster close social ties, a sense of unity, and a deep appreciation of cultural heritage. The Sasak cultural identity, shaped by religion and tradition, has been shown to help individuals navigate life's obstacles. However, the process of modernization and cultural shifts present obstacles in maintaining these highly respected traditions. This study shows that religion and local traditions play a significant role in shaping the psychological identity of the Sasak people. This study is expected to contribute to efforts to preserve culture and enrich understanding of the dynamics of psychological identity influenced by religious values ​​and traditions in local communities.